2011
DOI: 10.1007/s10995-011-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight and Prenatal Exposure to Indoor Pollution from Tobacco Smoke and Wood Fuel Smoke: A Matched Case–Control Study in Gaza Strip

Abstract: Maternal exposure to environmental tobacco smoke (ETS) is a major health hazard as it contains lower doses of the toxins that smokers' inhale. Prenatal exposure to wood fuel smoke has been linked to delivering low birth weight (LBW) infants. The study aims to assess the association between prenatal exposure to ETS and wood fuel smoke and LBW. A case-control study in ratio 1:1 was conducted in two hospitals with obstetric services in Gaza Strip. Subjects were selected during May-June and July-August 2007 from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
1
38
0
2
Order By: Relevance
“…In many countries, pregnant mothers are exposed to wood fuel smoke. The carbon monoxide depresses placental energy-dependent processes and amino-acid transport and exhibits a reduction of infants’ adjusted mean BW by −186 g (110). Variation in genes encoding enzymes modify the associations between maternal smoking and BW, but the contribution of epigenetic mechanisms, rather than genetic, underlie the long-term effects of smoke exposure as shown in aberrant placental metabolism, syncytial knot formation, or markers of placental oxidative damage (111).…”
Section: Resultsmentioning
confidence: 99%
“…In many countries, pregnant mothers are exposed to wood fuel smoke. The carbon monoxide depresses placental energy-dependent processes and amino-acid transport and exhibits a reduction of infants’ adjusted mean BW by −186 g (110). Variation in genes encoding enzymes modify the associations between maternal smoking and BW, but the contribution of epigenetic mechanisms, rather than genetic, underlie the long-term effects of smoke exposure as shown in aberrant placental metabolism, syncytial knot formation, or markers of placental oxidative damage (111).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies, including one RCT (analyzed per protocol) [52] and six observational studies [53-58] reported on the risk of low birth weight (<2500 gm at term), Additional File 3, Table 2. Two studies provided separate, independent estimates for pre-term IUGR and term LBW [54,57].…”
Section: Resultsmentioning
confidence: 99%
“…Pour évaluer l'impact du tabagisme passif sur la qualité de l'air, les particules respirables en suspension (PM 2,5 ) émises pendant la consommation de cigarettes et de pipes à eau ont été mesurées à l'intérieur et à l'extérieur de 18 lieux publics fumeurs et 5 lieux publics non-fumeurs de la ville de Gaza. Le taux de PM 2,5 moyen à l'intérieur des lieux fumeurs était de 117 µg/m 3 , un taux plus de quatre fois supérieur aux recommandations de l'Organisation mondiale de la Santé pour l'exposition quotidienne aux particules fines (25 µg/m 3 ).…”
Section: Tabagisme Passif Et Qualité De L'air Intérieur Dans Des Lieuunclassified
“…Particulate levels were also measured for 5 minutes outside each venue (immediately before indoor measurements) to account for ambient PM 2. 5 .…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation